Worldwide Genomic Diversity of the High-Risk Human Papillomavirus Types 31, 35, 52, and 58, Four Close Relatives of Human Papillomavirus Type 16 (2005)
ABSTRACT: Among the more than one hundred formally described human papillomavirus (HPV) types, 18 are referred to as high-risk HPV types due to their association with anogenital cancer. Despite pathogenic similarities, these types form three remotely related taxonomic groups. One of these groups is called HPV species 9 and is formed by HPV-16, the most common and best-studied type, together with HPV-31, -33, -35, -52, -58, and -67. Previous worldwide comparisons of HPV-16 samples showed about 2% nucleotide diversity between isolates, which were subsequently termed variants. The distribution of divergent variants has been found to correlate frequently with the geographic origin and the ethnicity of the infected patients and led to the concept of unique African, European, Asian, and Native American HPV-16 variants. In the current study, we address the question of whether geography and ethnicity also correlate with sequence variations found for HPV-31, -35, -52, and -58. This was done by sequencing the long control region in samples derived from Europe, Asia, and Africa, and from immigrant populations in North and South America. We observed maximal divergence between any two variants within each of these four HPV types ranging from 1.8 to 3.6% based on nucleotide exchanges and, occasionally, on insertions and deletions. Similar to the case with HPV-16, these mutations are not random but indicate a relationship between the variants in form of phylogenetic trees. An interesting example is presented by a 16-bp insert in select variants of HPV-35, which appears to have given rise to additional variants by nucleotide exchanges within the insert. All trees showed distinct phylogenetic topologies, ranging from dichotomic branching in the case of HPV-31 to star phylogenies of the other three types. No clear similarities between these types or between these types and HPV-16 exist. While variant branches in some types were specific for Europe, Africa, or East Asia, none of the four trees reflected human evolution and spread to the extent illustrated by HPV-16. One possible explanation is that the rare HPV types that we studied spread and thereby diversified more slowly than the more abundant HPV-16 and may have established much of today's variant diversity already before the worldwide spread of humans 100,000 years ago. Most variants had prototypic amino acid sequences within the E6 oncoprotein and a segment of the L1 capsid protein. Some had one, two, or three amino acid substitutions in these regions, which might indicate biological and pathogenic diversity between the variants of each HPV type.